The Development of a Pain Management and Discharge Planning Program for Caregivers of Terminally Ill Cancer Patients - Saengchalin, Prapaisri; Noihoon, Pichet; Worasuk, Nattanan (Thai Red Cross Nursing Journal, 2024)
This study aimed to develop a pain management and discharge planning program for caregivers of terminally ill cancer patients and to study the results of implementing this program. The study included two phases: 1) identifying and analyzing problems in order to develop a pain management program for family caregivers of terminally ill cancer patients upon being discharged to the home; this phase included focus group discussions with 12 persons, including doctors, pharmacists, nurses, nutritionists, and occupational therapists; and 2) evaluating both the effect of the program on the knowledge, attitudes, and pain management skills of caregivers as well as the pain levels of terminally ill cancer patients. The study involved the following four steps: 1. Participating in defining the problem and evaluating the situation, 2. Participating in reflection and thinking critically, 3. Choosing the right pain management approach, and 4 Evaluating and maintaining practices. The sample was composed of 35 family caregivers and 35 terminally ill cancer patients, selected via purposive sampling, conducted between July and December, 2023. The measurements of data collection were knowledge, attitude, and pain management skills questionnaires, and a numeric pain scale with a reliability of 0.73, 0.80, 0.76, and 0.87. Data were analyzed using percentages, mean, standard deviation, and paired t-tests. Qualitative data were analyzed using content analysis. The results showed that: 1st phase: After discussion with the multidisciplinary team, a pain management and discharge planning program for caregivers of terminally ill cancer patients was developed. 2nd phase: 1) After entering the program, the family caregivers had significantly higher mean scores regarding their knowledge, attitudes, and pain management skills than before entering the program (p < 0.01), and 2) terminally ill cancer patients had significantly lower mean pain scores, as both the minimum pain scores and maximum pain scores 24 hours post-training were significantly lower than before training (p < 0.01). Conclusions: The program developed through this study can be used to increase the capacity of caregivers to manage pain in terminally ill cancer patients upon discharge.